Alcohol from tropical fruit residues - Castro Gómez, Raúl J. H.; Tamburini, E. R.; Cal Vidal, José (Pesquisa Agropecuaria Brasileira, 2014)
Alcohol production from peel extracts of tropical fruits (banana, pineapple and mandarin oranges) having fermentable sugars extracted with hot water and HCl solutions (6.7% and a combined 35% and 41%) was studied. For the fermentation of the extract the yeast Saccharomyces cerevisiae was used. The sugar utilization varied from 96% to 100% for hot water extraction being this value lower for the HCl extractions. Alcohol productions were 12.6 liters per ton in the case of banana, 68.7 liters per ton for mandarins, and 100.6 liters per ton for pineapple, for the hot water extractions. These values dropped to 12 liters per ton in banana, 10 liters per ton in pineapple and 26 liters per ton in orange peels for the diluted acid extraction. For an extraction process using a combination of hot water and concentrated acid, yields were 13 l/ton for pineapple, 9.5 l/ton for mandarin and 7.8 l/ton for banana peels. The alcoholic yields were estimated as 72.1% for banana, 98.2% for pineapple and 98.0% for mandarins, for the hot water extraction. These values were reduced to 59%, 34% and 43%, respectively, in the diluted acid extraction, and to 64.3%, 32.9% and 65.1% in the same order, for the combined process.